Exposure to persistent organochlorine compounds through fish consumption and the incidence of osteoporotic fractures - Wallin, Ewa; Rylander, Lars; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'Animal studies have shown that persistent organochlorine compounds (POC) impair normal bone metabolism and result in increased bone fragility. These findings may have health implications for POC-exposed human populations. The aim of the present study was to assess the impact of POC-contaminated fish on the self-reported fracture incidence of Swedish fishermen and their wives. ' ' METHODS ': 'A postal questionnaire was sent to 2096 fishermen and 1602 fishermen`s wives from the Swedish east (exposed) coast and 4584 fishermen and 4217 fishermen`s wives from the west (unexposed) coast. Self-reported fractures, together with specified current fish consumption and information about potential confounders, were registered. The response rates varied between 50% and 59%. The age distributions of the nonrespondents and respondents were almost identical. Hip, vertebral, and wrist fractures were classified as osteoporotic. The fracture incidence rates for specific skeletal locations were based on allocated fractures and person-years under risk from the age of 25 years until the time of fracture or the end of follow-up. ' ' RESULTS ': 'No differences in fracture incidence were observed between the east and west-coast cohorts. East-coast wives with more than one meal of fatty fish from the Baltic Sea per month had, however, an increased fracture incidence as compared with that of the east-coast wives who ate, at most, one such meal per month (age-adjusted incidence rate ratio 1.68, 95% confidence interval 1.00-2.84). No such exposure-response association was found for the fishermen. ' ' CONCLUSIONS ': 'The present study only minimally supports an association between POC exposure through contaminated fish and an increased risk of osteoporotic fractures.
Keywords: exposure; fish consumption; fisherman; fracture; incidence; osteoporosis; osteoporotic fracture; PCP; persistent organochlorine compound; polychlorinated biphenyl